The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.nlm.2017.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Impaired extinction of cued fear memory and abnormal dendritic morphology in the prelimbic and infralimbic cortices in VPAC2 receptor (VIPR2)-deficient mice

Abstract: The structurally related neuropeptides vasoactive intestinal peptide (VIP) and pituitary adenylate cyclase-activating polypeptide (PACAP) have been implicated in stress regulation and learning and memory. Several bodies of research have shown the impact of the PACAP specific receptor PAC1 on fear memory, but the roles of other PACAP receptors in regulating fear stress responses remain to be elucidated. Here we aimed to investigate the effects of genetic deletion of VIPR2 encoding the VPAC2 receptor, which bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 85 publications
0
19
0
Order By: Relevance
“…Overall, the results suggest that the activation of the VPAC2 receptor delays or limits the maturation in mouse cortical neurons. In a previous study, we also found that adult VPAC2 receptor knockout mice show abnormal dendritic morphology in the prelimbic and infralimbic cortices, but not basolateral amygdala (Ago et al, 2017). Loss of the VPAC2 receptor reorganized apical and basal dendritic arbors of prelimbic cortex neurons and apical, but not basal, dendritic arbors of infralimbic cortex neurons.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Overall, the results suggest that the activation of the VPAC2 receptor delays or limits the maturation in mouse cortical neurons. In a previous study, we also found that adult VPAC2 receptor knockout mice show abnormal dendritic morphology in the prelimbic and infralimbic cortices, but not basolateral amygdala (Ago et al, 2017). Loss of the VPAC2 receptor reorganized apical and basal dendritic arbors of prelimbic cortex neurons and apical, but not basal, dendritic arbors of infralimbic cortex neurons.…”
Section: Discussionmentioning
confidence: 52%
“…Recently, Tian et al (2019) have developed a conditional human VIPR2 CNV bacterial artificial chromosome (BAC) transgenic (hVIPR2-BAC tg) mouse model of VIPR2 CNV, and they reported that hVIPR2-BAC tg mice showed cognitive, sensorimotor gating, and social behavioral deficits and decrease in the complexity of dendritic arborization of the striatal spiny projection neurons. Additionally, VPAC2 receptor knockout mice have abnormal dendritic morphology of the prefrontal cortex neurons, but not basolateral amygdala neurons (Ago et al, 2017). These findings suggest that the VPAC2 receptor plays an important role in the regulation of the dendritic morphology and overactivation of the VPAC2 receptor might impair neural development in the brain.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…VIP play diverse roles in the central nervous system, including the control of circadian rhythms, learning and memory, psychiatric illness, and responses to stress [30]. Vipr2 ( Vpac2 ) knockout mouse lacks circadian control [30] and also exhibits impaired extinction of cued fear memory and regulation of the dendritic morphology [31]. VIPR2 is located in the subtelomeric region of chromosome 7 and VIPR2 duplications were indicated in the etiology of autism [32].…”
Section: Discussionmentioning
confidence: 99%
“…Pituitary adenylate cyclase-activating polypeptide can also influence memory via modulation of intrinsic physiology (see Open Questions) and via developmental maturation of memory circuits (reviewed in Shen et al, 2013 ). For example, developmental knockout of VPAC2 which is sensitive to both VIP and PACAP prevented the formation of fear extinction memory in adulthood ( Ago et al, 2017 ). Importantly, VPAC2-KO mice had reduced cell size and dendritic branching in the prelimbic cortex, morphological changes similar to those observed after chronic corticosterone exposure and chronic stress, conditions which also produce fear extinction deficits ( Wellman, 2001 ; Radley et al, 2004 , 2006 ; Moench and Wellman, 2017 ; reviewed in Wellman et al, 2020 ).…”
Section: Cellular and Synaptic Physiologymentioning
confidence: 99%